Risk and liquidity in a system context - Shin, Hyun Song (Journal of Financial Intermediation, 2008)
This paper explores the pricing of debt in a financial system where the assets that borrowers hold to meet their obligations include claims against other borrowers. Assessing financial claims in a system context captures features that are missing in a partial equilibrium setting, such as liquidity spillovers across financial institutions resulting from expansions and contractions of balance sheets. Aggregate liquidity can be seen as the rate of growth of financial sector balance sheets.